Implementation of Flipbook-Based E-Modules on Particle Kinematics Material for Physics Learning in High Schools - Kistiono; Fitri, Ade (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
This research aims to develop a flipbook-based e-module on particle kinematics for high school physics learning. The research employed the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The analysis phase revealed that 58% of students encountered difficulties in learning physics, while 50.7% specifically struggled with force-related materials. The e-module was developed based on student needs and validated by content, design, and language experts. Validation results indicated that the e-module was suitable for use after incorporating suggested revisions. Practicality testing was conducted in two phases: a limited trial involving 18 students and a broader implementation with 35 students. The average practicality level reached 81.2% in the limited trial and 80.6% in the broader implementation, categorizing the e-module as